Архиепископот Лав Охридски и судирот со Латините во неговата епоха - Nedeski, Viktor (Православен богословски факултет „Св. Климент Охридски“ Скопје, 2016)
Leo the Archbishop of Ohrid has sent a letter with theological content to the Bishop John of Trania in Apuleia in 1053 with an aim to protect the Christians in South Italy from the Latin liturgical practices. In the letter he addrerssed all the Western Bishops and the Pope himself. He aimed to show that certain worship practices of the Western Church, were not Christian customs and should therefore be rectified. The Archbishop and cardinal Humbert of Silva Candida translated to Latin the letter of Leon when he was in Apulia and gave it to the Pope of Rome, Leo IX. As a consequence from this action on 16 April 1054 during the Vespers the representatives of the Pope have entered into the church of Saint Sophia in Constantinople and put on the Altar Table a Papal bull (decree) with anathema for the Patriarch Michael Cerularius and the archbishop Leo of Ohrid. Thus one theological text became a reason for a historical event with millennial consequences – the schism from 1054 which continues until today.
Keywords: Лав Охридски, Охридска архиепископија, Латинска теологија